Reconstrucción y funcionamiento de horno crisol para fundición de chatarra de aluminio en Ayacucho - Cossio Herrera, Luis Alberto (2024)
The general objective was to rebuild and put into operation the crucible furnace for smelting aluminum scrap at the National University of San Cristóbal de Huamanga – Ayacucho. The specific objectives were to evaluate the stages of the reconstruction regarding the modification of the design and operation of the crucible furnace for the smelting of aluminum scrap. Obtaining objects (finished products) through different molding techniques. Carry out material and energy balances using oil and gas as fuel. The level of research was technological experimental, and the analytical method was comparative. The design was explanatory experimental. 4 tests were carried out using oil as liquid fuel, then gas, thereby improving the aluminum smelting process, with a high recovery percentage. It was implemented with an automated control panel for the use of gas as fuel. Different molding techniques were also experimented with. The material balance, calculations of the kiln load and products, calculation of the fed air and gases leaving the kiln were carried out. It is recommended to continue with other research in the field of transformative metallurgy since one way to reduce aluminum pollution is by recycling it, which is why it is considered a sustainable metal.